Concurrent Retropharyngeal and Cervical (Colli) Abscess in a Three-Year-Old Child: Diagnostic Challenges, Multidisciplinary Management, and Favourable Surgical Outcome - Ketut Tadeus Max Nurcahya Pinatih; I Gusti Ayu Mahaprani Danastri; M. Ayu Damayanthi; Putu Dian Ariyanti Putri (Sriwijaya Journal of Otorhinolaryngology, 2026)
Background: Retropharyngeal abscess is an uncommon but potentially life-threatening deep neck space infection of early childhood that may compromise the airway and, when it extends into adjacent compartments, endanger the great cervical vessels; its coexistence with a concurrent cervical (colli) abscess and carotid-space involvement in a toddler is rarely documented. Objective: This report describes the diagnostic reasoning, the multidisciplinary airway-centred management, and the favourable outcome of such a case. Case presentation: A three-year-old boy presented with a twenty-day history of a progressively enlarging, erythematous left neck swelling and a fourteen-day history of intermittent fever unresponsive to oral antibiotics, followed by vomiting of blood-stained pus. He was febrile with a muffled voice and a tender, warm, non-fluctuant left cervical mass. The leukocyte count was elevated and haemoglobin mildly reduced. Contrast-enhanced computed tomography showed a rim-enhancing retropharyngeal collection extending to the carotid space and left neck, abutting the left carotid artery and displacing the trachea, with cervical lymphadenopathy, pan-sinusitis, and pneumonia. After two negative SARS-CoV-2 tests, incision and drainage under general anaesthesia with a secured airway evacuated pus from the cervical component, supported by intravenous ceftriaxone and metronidazole; the child recovered fully. Conclusion: Delayed recognition of paediatric deep neck infection permits dangerous multicompartment spread; integrated imaging-operative judgement and airway-focused multidisciplinary care are the decisive determinants of a favourable outcome.